2015
DOI: 10.1002/aenm.201502095
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Functional Iron‐Only Electrodes for Efficient Water Splitting with Enhanced Stability through In Situ Electrochemical Regeneration

Abstract: are the indirect conversion of solar into chemical energy using a photovoltaic (PV)-electrolyzer [ 9,10 ] system and its direct conversion with a photoelectrochemical (PEC) cell. [11][12][13] The International Energy Agency identifi ed a key obstacle to the widespread implementation of water splitting technologies to be the development of cheap and active materials to catalyze both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), which operate under identical and mild conditions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 52 publications
1
97
0
Order By: Relevance
“…Manganese oxides based OER electrocatalysts as a model system for the oxygen evolving complex of photosystem II were frequently studied and based on head space measurements the Faradaic efficiency amounted to 78% after 90 min of OER in pH controlled Na 2 SO 4 [60] . The charge to oxygen conversion rates of recently developed full water splitting electrocatalysts determined in alkaline solution ranged between 95.8 and 100% [109,110,112] . A comparison of the OER properties of Ni42-300 at pH 7 with the corresponding characteristics of noble metal containing catalysts is a sine qua for an in-depth evaluation of the electrocatalytic characteristics of our material.…”
Section: Resultsmentioning
confidence: 99%
“…Manganese oxides based OER electrocatalysts as a model system for the oxygen evolving complex of photosystem II were frequently studied and based on head space measurements the Faradaic efficiency amounted to 78% after 90 min of OER in pH controlled Na 2 SO 4 [60] . The charge to oxygen conversion rates of recently developed full water splitting electrocatalysts determined in alkaline solution ranged between 95.8 and 100% [109,110,112] . A comparison of the OER properties of Ni42-300 at pH 7 with the corresponding characteristics of noble metal containing catalysts is a sine qua for an in-depth evaluation of the electrocatalytic characteristics of our material.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Thec urrent state-of-the-art catalysts that perform both the OER and HER are based on noble metals,which are unsuitable for practical large-scale applications owing to their scarcity and high cost. [5] Among these are cheap transitionmetal-based materials,including oxides, [2a,c-f] chalcogenides, [6] and pnictides, [6b,7] which have been explored as alternative OER, HER, and overall water-splitting catalysts. [5] Among these are cheap transitionmetal-based materials,including oxides, [2a,c-f] chalcogenides, [6] and pnictides, [6b,7] which have been explored as alternative OER, HER, and overall water-splitting catalysts.…”
mentioning
confidence: 99%
“…[6] In early 2017, Gao et al reported using FeSe 2 for the OER with ac onsiderably low overpotential of 330 mV at ac urrent density of 10 mA cm À2 . [6] In early 2017, Gao et al reported using FeSe 2 for the OER with ac onsiderably low overpotential of 330 mV at ac urrent density of 10 mA cm À2 .…”
mentioning
confidence: 99%
“…In 2015, Shi and co-workers [17] reported aN i-Fe layered double hydroxide (LDH) on three-dimensional electrochemically reduced graphene oxide that exhibited as mall overpotential of h = 259 mV at 10 mA cm À2 and alow Tafel slope of 39 mV decade À1 . [51,52] Herein we report that Cu 2 On anowires (NWs),f abricated on aC F( denoted as Cu 2 ON Ws/CF) by an eco-friendly and facile electrochemical method, were loaded with an advanced NiFe electrocatalyst to form ah ighly efficient three-dimensional anode (NiFe/Cu 2 ON Ws/CF;S cheme 1). In particular,m acroporous Cu foam (CF) has great advantages owing to its low cost and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%